A Survey of Curriculum Topics Relevant to the Practice of Management Accounting. - Deakin Ill, Edward B.; Summers, Edward L. (The Accounting Review, 1975)
There has been a great deal of interest expressed in the development of accounting curricula for students wishing to pursue a career in management accounting, as of April 1975. At University of Texas in Austin, Texas, it was felt that practitioners in the management accounting field should be consulted to determine their perceptions of the usefulness of various management accounting topics in their work experiences. A group of faculty met to consider what topics should be included in such a survey. A list of thirty-nine topics was chosen from consulting the indexes and table of contents in several managerial and cost accounting texts, as well as from discussion with a small group of management accounting practitioners. An analysis of the results of the survey indicated there were five major rank-order groups of topics, namely, performance evaluation, responsibility accounting, internal control, tax factors in business decisions and profit planning and control. These groups were determined by searching for gaps between topics in the scale-weighted averages.